DILEMA DUNIA PENDIDIKAN NASIONAL - Zulfakar Zulfakar (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2018)
The changes that have occurred have shifted the order of life and the views of thepeople. Materialism, capitalism, efficiency, and effectiveness, have become the purpose andspirit of life. Shifting people's views, has also changed the view of success and quality ofeducation, where education is measured by success in the absorption of graduates in the worldof work, therefore, education is analyzed from the characteristics of investment. Shifting themeaning and responsibility of education, encouraging the world of education to reform withalternatives: building renewal of reasoning of its citizens, towards independence and maturity,education is carried out comprehensively and collaboratively, with all parties in partnership,and build a vision of education comprehensively and simultaneously, with all parties.Keywords: Dilemma, World of National Education